High pressure processing improves the texture quality of fermented minced pepper by maintaining pectin characteristics during storage. Issue 6 (19th May 2022) - Chen, Fei; Chen, Yuyu; Wang, Yingrui; Ding, Shenghua; Qin, Yeyou; Jiang, Liwen; Wang, Rongrong
Abstract : Abstract: Texture quality affects the sensory and market acceptance of fermentation minced pepper (FMP), but it will deteriorate during storage. Thus, high pressure processing (HPP) and thermal pasteurization (TP) were used to improve the texture quality of FMP during storage. The results showed that variations in texture quality and pectin characteristics under HPP and TP treatments were similar during storage. The hardness, cell wall material (CWM) and sodium carbonate‐soluble pectin (SSP) content, water‐soluble pectin (WSP) molecular weight ( M w ) decreased, while WSP content and sodium chelate‐soluble pectin (CSP) M w increased after storage. HPP‐treated FMP showed higher hardness (66.64–85.95 N) than that in TP‐treated one (57.23–62.72 N) during storage. Rhamnose (Rha), arabinose, mannose, and glucose were the crucial compositions in three pectins, and their total molar ratios, respectively, reached 89.19% and 87.97% after HPP and TP treatment. However, the molar ratio of most monosaccharide in three pectins decreased after storage. Atomic force microscope images indicated the short chains and branch structures increased but aggregates decreased in most pectin components during storage. Pearson correlation analysis demonstrated FMP hardness was extremely ( p  < 0.01) positively correlated with CWM and SSP content, and extremely ( p  < 0.01) negatively correlated with WSP content. Compared to TP treatment, HPP presented higher hardness, SSP content and M w, Rha content, CSP M w, and lower WSP content during storage. Hence, HPP was an effective method to improve the texture quality of FMP by maintaining pectin characteristics during storage. Practical Application: Softening is one of the main factors affecting market value and consumer preferences for FMP, and it is closely related to the modification and depolymerization of pectin. Changes of texture quality and pectin properties in HPP‐ and TP‐treated FMP during storage were assessed, including hardness, the content, monosaccharide compositions, M w distribution, and nanostructure of WSP, SSP, and CSP. Compared to TP treatment, HPP could effectively improve the texture quality of FMP by inhibiting pectin degradation during storage. All the findings presented in this study would help to provide new insights into regulating the texture quality of FMP.